The phytochemical and pharmacological properties of artocarpin from Artocarpus heterophyllus - Nik Nurul Najihah Nik Mat Daud; Abdi Wira Septama; Nordin Simbak; Eldiza Puji Rahmi (Asian Pacific Journal of Tropical Medicine, 2020)
Artocarpus heterophyllus Lam. (Moraceae) has been traditionally used in treating various diseases such as diabetes, diarrhea, malarial fever, inflammation, wound healing and other diseases. Since various bioactive compounds have been found in this plant, this review focuses on the phytochemical and pharmacological properties of a potent bioactive compound artocarpin. Despite its various functions, a mechanistic review on this compound has not been reviewed specifically. Here, pharmacological studies in vitro and in vivo on artocarpin are discussed thoroughly stressing on anticancer, antimicrobial, anti-tyrosinase, antioxidant and antiinflammatory aspects of artocarpin. This review would be beneficial for future study to show the competency of natural products for their therapeutic characteristics.